Oscar Romero dan John Prior: Model Imam Terlibat - Yosef Keladu Koten; Ignas Ledot; Kris Ibu (JURNAL LEDALERO, 2023)
This article aims to introduce two inspiring figures or models of involved priests, namely Oscar Romero and John Prior. Through comparative analysis of qualitative data, it is discovered that there are differences between Romero and John in terms of historical background, context, and methods or forms of involvement. Romero was a priest who later became a bishop and faced the authoritarian government in El Salvador, while Prior was a priest and intellectual who was concerned with the internal realities of the Church in Indonesia. Romero used the method of preaching and prophetic discourse, while John’s method is sharing the Scriptures. Despite these differences, both are two inspirational figures who contextualize their faith in God by being in solidarity with and living with the poor. The suffering experienced by the marginalized has honed the sensitivity to act and the ability to go beyond the boundaries of social partition. They do not confine themselves to a sacred space and stay away from the profane world, but instead merge themselves into the midst of people who are marginalized either by an oppressive regime or by stigmatization. Romero and John are models of involved priests because for them involvement with the marginalized is a form of priestly accountability before God and the people they serve.Key words : involved priest, profile, method, Oscar Romero, John Prior